Use of AMH in the Differential Diagnosis of Anovulatory Disorders Including PCOS - Capuzzo, Martina; La Marca, Antonio (Frontiers in Endocrinology, 2021)
Since the historical use of gonadotrophin and estradiol levels to define the different anovulatory disorders has shown some limitations, the use of other markers such as anti-müllerian hormone (AMH) has been proposed. This review addresses the role of AMH in the differential diagnosis of anovulatory disorders, especially focusing on its value in the prognostic characterization of their severity. Current limitations and future clinical applications are discussed.